PENGENDALIAN PERSEDIAAN KAYU MAHONI UNTUK MENGOPTIMALKAN STOK PADA DEPARTEMEN SAWMILL PT CHIA JIANN INDONESIA FURNITURE (Science and Technology (SciTech), 2023)
PT Chia Jiann Indonesia Furniture is one of the manufacturing companies in Jepara. The main raw material used for production is mahogany wood, but the inventory of raw materials at PT Chia Jiann Indonesia Furniture has not been well planned which results in mahogany wood inventory in the company is not optimal.  Based on these problems, this research will use the EOQ (Economic Order Quantity) method and the POQ (Period Order Quantity) method. This method can calculate the inventory of mahogany raw materials in the company to be minimum and more efficient so that the company can get maximum profit. The results of this study show that the calculation  of Total Inventory Cost (TIC) using the EOQ method is Rp.  134,405,772 and Total Inventory  Cost (TIC) using the POQ method is Rp.  118,500,000. The use of the POQ method has a smaller Total Inventory Cost (TIC) when compared to using the EOQ method and company policies for mahogany raw materials, so that if you use the POQ method the company will save Rp. 9,750,000. So, the inventory control method at PT Chia Jiann Indonesia Furniture should be done with the POQ method.